2021
DOI: 10.1007/s43615-021-00110-4
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Perspective of Materials, Practices and Structures Within the Food, Energy and Water Nexus of Australian Urban Alternative Food Networks

Abstract: Established and emerging alternative food networks (AFNs) are providing developments to circular economy within the Australian urban food system. In identifying and evaluating areas of AFNs providing positive externalities contributing to circularity, this systematic review provided an engineering and management science perspective on AFNs. Key foci were urban agriculture, emergent technologies, community gardens and prosumer practices and how their use of food, energy and water affect sustainability, ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Moreover, past research showed the contribution of fuel emissions as only a relatively small fraction (7%) of total emission, with a much larger proportion of emissions generated from activities like energy use during irrigation, production and postharvest activities, pesticide and fertiliser use, further investigation is needed in the UA context to understand and quantify these emissions, particularly to determine if they are the same, higher or lower than large scale commercial agriculture per unit of produce. A study of the circular economy benefits of Alternative Food Networks (AFNs) in Australia showed the potential to reduce environmental problems [79]. The results of this study suggest that conventional approaches (e.g., distributing to centralised markets) may not deliver the intended outcomes, and future studies may include the impacts of such alternative movements (such as AFNs), which may create overall economic, environmental and social benefits from more localised distribution chains.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, past research showed the contribution of fuel emissions as only a relatively small fraction (7%) of total emission, with a much larger proportion of emissions generated from activities like energy use during irrigation, production and postharvest activities, pesticide and fertiliser use, further investigation is needed in the UA context to understand and quantify these emissions, particularly to determine if they are the same, higher or lower than large scale commercial agriculture per unit of produce. A study of the circular economy benefits of Alternative Food Networks (AFNs) in Australia showed the potential to reduce environmental problems [79]. The results of this study suggest that conventional approaches (e.g., distributing to centralised markets) may not deliver the intended outcomes, and future studies may include the impacts of such alternative movements (such as AFNs), which may create overall economic, environmental and social benefits from more localised distribution chains.…”
Section: Discussionmentioning
confidence: 91%
“…Alternative food networks (AFNs) have emerged in response to these glaring challenges. Activists have mapped out different ways of addressing these challenges by creating new spaces for the production, consumption and trading of food, whose alternative ethical features (e.g., organic, fair trade, local, quality, slow) distinguish them from conventional products [ 3 , 4 ]).…”
Section: Introductionmentioning
confidence: 99%